EVALUATION OF HAZARD INDICES OF BACKGROUND RADIATION IN SOME MAJOR TOWNS OF GOMBE STATE, NIGERIA - A, ABDULKADIR; H, SEYDOU; A. D, BAJOGA; A, ANDREW (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Interest for the determination of naturally occurring radiation and environmental radioactivity has led to the interest of extensive surveys in many countries including Nigeria. This work was carried out to ascertain the indoor and outdoor background ionizing radiation in Gombe state as a precautionary measure due to recent development of radioactive activities in the State. RDS-31 Survey meter placed 1m above the earth surface was used for taking readings. The measured average exposure rates ranged from 0.007 to 0.017 mR/h for indoor and 0.007 to 0.015 mR/h for outdoor with a total mean of 0.010 ± 0.003 mR/h, which are within the limit of world average of 0.013 mR/h. The indoor absorbed dose rate ranged from 61.34 ± 7.52 nGy/h in Kwami to 149.21 ± 57.35 nGy/h in Billiri with a total mean value of 88.47 ± 32.64 nGy/h, which is higher than World’s average of 84.00 nGy/h, while the outdoor ranged from 61.34 ± 17.45 nGy/h in Shongom to 134.42 ± 38.61 nGy/h in Kaltungo with a mean total value of 90.24 ± 29.88 nGy/h, which is 31.24 nGy/h higher than the standard average of 59.00 nGy/h. Equivalent dose rate was calculated to be in the range of 0.59 ± 0.07 mSv/yr to 1.44 ± 0.55 mSv/yr with a total mean of 0.86 ± 0.32 mSv/yr, which is within the International Commission on Radiological Protection(ICRP)recommended limit of 1 mSv/yr. The AEDE shows a range of 0.33 ± 0.08 to 0.73 ± 0.28 mSv/yr for indoor and 0.08 ± 0.02 to 0.16 ± 0.05 mSv/y for the outdoor respectively. The sum is found to be 0.54 mSv/yr which is 0.02 mSv/yr higher than the world’s average of 0.52 mSv/yr. Estimated life-time cancer risk ranges from 1.20 x 10-3 to 2.56 x 10-3 mSv/yr, while outdoor ranges from 0.30 x 10-3 to 0.58 x 10-3mSv/yr with a total mean of 2.08 x 10-3 mSv/yr which is larger compared with the resulting worldwide average of 1.45 x 10-3. The excess lifetime cancer risk values indicated that the probabilities of contracting cancer for residents of Gombe, Kwami, Dukku, Yamaltu Deba, Bajoga, Shongom, Balanga, Funakaye, Kaltungo are low but higher in Billiri, and Akko (Mai-Ganga). These values may not constitute any immediate health risk to the residents of Gombe state but precaution should be taken in order to avoid stochastic effect.